Hippocampal Volumes in Preterm Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The relation between neonatal regional brain volumes and working memory deficits at age 2 years was investigated in 156 very preterm children born at the Royal Women's Hospital, Melbourne, Auatralia, prior to 30 weeks gestation or weighing <1250g.